Thermal and conductivity studies of chitosan acetate-based polymer electrolytes - Osman, Z. (2005)
Thermogravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC) have been employed to study the thermal stability of the chitosan acetate-based polymer electrolyte films. The glass transition temperature, T-g measurements confirm the conductivity enhancement effect by adding the plasticizer and salt in the chitosan acetate films